Perengkahan Katalitik Palm Fatty Acid Distillate Menjadi Biofuel Menggunakan Katalis Natrium Karbonat Dengan Variasi Temperatur Dan Konsentrasi Katalis Natrium Karbonat - Muhammad Yusro Annur; Yelmida Yelmida; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Oil Fuel consumption in indonesia is very high and keep increasing every year, but not in balance with total supplies of fuel oil so biofuel as alternative fuel is needed. Biofuels can be produced by catalytic process palm fatty acids destilat (PFAD) using catalysts sodium carbonate (Na2CO3). The purpose of this research it to get highest yield in the process of making biofuel with variations of temperature (350oC – 430oC), concentration catalyst (0,5-2,5 % wt), weight feed PFAD 150 grams and flow rate of N2 150 ml/s. The results test of catalytic process obtained by conversion highest value of 37,66 % in temperature 410 oC and catalyst concentration Na2CO3 2% wt. wiht composition 38,37% gasoline, 12,79% kerosene and 30,61% diesel, while at catalyst concentration Na2CO3 1% wt. obtained yield 31,77% with composition 38,37% gasoline, 12,79% kerosene and 30,61% diesel. Dominant composition results in this research are kerosene and gasoline fraction.Keyword : Biofuel, Cracking, Gasoline, Kerosene, PFAD